Strategi Promosi Resto “Erista Griyo Dhahar” dalam Membangun Brand Awareness - Bambang Sujarwadi; Dhety Chusumastuti; Tanaya Kanani Benedikta (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2025)
The number of businesses in the culinary sector has been steadily increasing, especially after the COVID pandemic. Therefore, promotional strategies are crucial, particularly for building brand awareness in the business world. "Erista Griyo Dhahar," a restaurant located in Pakem, Yogyakarta, implements promotional strategies to build brand awareness. This study aims to analyze the promotional strategies used by "Erista Griyo Dhahar" to enhance brand awareness. The research employs a qualitative method with data collection techniques including interviews, observations, and documentation. The theoretical framework used is the Promotional Mix which includes advertising, personal selling, sales promotion, Public Relations, and direct marketing for building brand awareness for "Erista Griyo Dhahar." The results of the study indicate that "Erista Griyo Dhahar" combines all five aspects of the promotional mix as part of its strategy to build brand awareness. However, advertising and personal selling are found to be the most effective, as evidenced by the restaurant's increasing sales each year. The brand awareness of "Erista Griyo Dhahar" is at the level of brand brand recognition. Recommendations for "Erista Griyo Dhahar" include increasing engagement on social media, maintaining personal selling activities, creating more engaging promotions, conducting Public Relations activities in a routine and structured manner, and developing appealing and persuasive copywriting.